Strengthening Islamic Values for Attitude Change of Students through the Majelis Anak Saleh (MAS) Program at UPTD SD Negeri 3 Parepare - Tamsil; Muhammad Saleh; Usman; Sitti Nurhayati; Ahdar (Universitas Muhammadiyah Palu, 2024)
This research aims to describe the form of strengthening Islamic values practiced by students at UPTD SDN 3 Parepare, the implementation of the Saleh Children's Assembly program and changes in attitudes that are formed in students after participating in the Saleh Children's Assembly program at UPTD SDN 3 Parepare. The method used is field research, namely research in which data is obtained by conducting field surveys. Data collection techniques used include observation, interviews, and documentation studies, with data analysis techniques. The results of the research show that the Islamic values practiced by UPTD SDN 3 Parepare students have been implemented but are not optimal because they have not been programmed well. The implementation of the Saleh Children's Assembly program at UPTD SDN 3 Parepare is intended to optimize Islamic values that have been practiced in aspects of worship, morals and developing Islamic artistic talent. The changes in attitudes that are formed after participating in the MAS program are (1) Aspects of worship; getting students used to reading and memorizing the Al-Qur'an, students being comfortable, calm and motivated in learning, students full of a sense of responsibility and discipline in carrying out Zuhr and Dhuha prayers. (2) Moral aspects; Changes can be seen from students becoming more respectful, polite and courteous in speaking to both fellow students and teachers, having a humble attitude towards teachers, respecting and respecting each other. (3) Aspects of developing Islamic artistic talent; Students have high self-confidence, develop an attitude of responsibility and independence in carrying out their duties, have high enthusiasm and are more optimistic. Changes in students' attitudes through the MAS program at UPTD SDN 3 Parepare through aspects of worship, morals and developing Islamic artistic talents can optimize and strengthen Islamic values towards changes in students' attitudes both in quantity and quality.